Spoligotypes of Mycobacterium tuberculosis from Different Provinces of China - Dong, Haiyan (American Society for Microbiology (ASM), 2010)
A total of 2,346 Mycobacterium tuberculosis isolates from 13 provinces in China were genotyped by spoligotyping. Two hundred seventy-eight spoligotypes were identified: 2,153 isolates were grouped into 85 clusters, and the remaining 193 isolates were orphans. Comparison with the SpolDB4.0 database revealed that 118 spoligotypes had shared international type numbers in the database and the other 160 were novel. These 160 novel spoligotypes were assigned to families and subfamilies using the SpotClust program. The most prevalent family was the Beijing family (74.08%), followed by the T family (14.11%). CAS family strains were found only in the Xinjiang and Tibet regions, while EAI family strains were found only in Fujian Province. In conclusion, the present study of the M. tuberculosis population in China demonstrated that Beijing family isolates are the most prevalent strains in China and that they exhibit geographical variation. Furthermore, many new spoligotypes were found in this study.